Tremont House at Tremont and Beacon Streets, ca. 1860-90 - Unknown (Tufts Archival Research Center, 2005)
Elevated view northeast of Tremont House, located at the southwest corner of Tremont and Beacon Streets. The facade of the hotel faces east-southeast. The south-southwest elevation of Tremont House faces the Granary Burial Ground, which is included along the lower-left side of the image. Street lights line the sidewalk along Tremont Street. Horse-drawn carriages and street railroads are included in the photograph. Tremont House designed by Isaiah Rogers, 1828; demolished, ca. 1890 3 1/8 x 2 15/16 Albumen prints